Barriers to enrollment in pulmonary rehabilitation in a private hospital in Brazil: a physician survey study - Gushken, Fernanda; Degani-Costa , Luiza Helena; Colognes, Thaíz Carolina Pimentel; Rodrigues , Maíra Thomazini; Zanetti , Mayra; Bonamigo Filho, José Luiz; Matos, Luciana Diniz Nagem Janot De (Revista de Medicina, 2020)
Introduction: Pulmonary rehabilitation (PR) plays a key role in the management of chronic lung diseases, but it remains largely underused worldwide. The aim of this study was to assess clinicians’ knowledge about PR and to identify the barriers they encounter when referring patients with medical insurance to PR in a private hospital in Brazil. Methodology: This was a survey-based cross-sectional study conducted in 2019 at a reference hospital in São Paulo, Brazil. Eligible participants were physicians registered with the following specialties: Internal Medicine, Geriatrics, Cardiology, Pulmonology or Thoracic Surgery. Results: We collected 72 responses. While 99% of participants recognized COPD as a potential indication for PR, interstitial lung disease, bronchiectasis and pulmonary hypertension were less often recognized (75%). Most participants (67%) incorrectly associated PR with lung function improvement, while 28% of cardiologists and 35% of internists/geriatricians failed to recognize benefits on mood disorders. Notably, 18% of participants recommended PR only to patients on supplemental oxygen and 14% prescribed only home physiotherapy, patterns more commonly seen among non-respiratory physicians. The 3 most perceived barriers to referral and adherence were health insurance coverage (79%), transportation to the PR center (63%) and lack of social support (29%). Conclusions: Financial, logistic and social constraints pose challenges to PR enrollment even for patients with premium healthcare insurance plans. Moreover, physician knowledge gaps may be an additional barrier to PR referral and uptake. Providing continued medical education, incorporating automatic reminders in electronic medical records and using telerehabilitation tools may improve PR referral, adherence and ultimately patient care.